2014
DOI: 10.4137/dti.s13529
|View full text |Cite
|
Sign up to set email alerts
|

In SilicoMolecular Characterization of Cysteine Protease YopT fromYersinia pestisby Homology Modeling and Binding Site Identification

Abstract: Plague is a major health concern and Yersinia pestis plays the central causal role in this disease. Yersinia pestis has developed resistance against the commonly available drugs. So, it is now a key concern to find a new drug target. Cysteine protease YopT enzyme is an important factor used by Yersinia pestis for pathogenesis in its host and it has the anti-phagocytic function of removal of C-termini lipid modification. The 3D structure of cysteine protease YopT of Yersinia pestis was determined by means of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Homology models are quite often generated for much smaller systems. 20,[37][38][39] Typically when homology models are developed for large system it is in combination with cryo-electron microscopy, and individual pieces of the model are fit into the larger overall surface map. 4,40 In this work, even though we developed a very large scale homology model independently of cyro-electron microscopy data, the model proves to be useful for accurate prediction of epitope regions in THSD7A, as it is corroborated by the work of Seifert.…”
Section: Seifert Et Al Also Utilized Two Domain Truncations Of the Tmentioning
confidence: 99%
“…Homology models are quite often generated for much smaller systems. 20,[37][38][39] Typically when homology models are developed for large system it is in combination with cryo-electron microscopy, and individual pieces of the model are fit into the larger overall surface map. 4,40 In this work, even though we developed a very large scale homology model independently of cyro-electron microscopy data, the model proves to be useful for accurate prediction of epitope regions in THSD7A, as it is corroborated by the work of Seifert.…”
Section: Seifert Et Al Also Utilized Two Domain Truncations Of the Tmentioning
confidence: 99%
“…4 ). Parameters, such as residue in the favored, allowed, and generously allowed region and G-factor, are the determinants of a good model [ 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we subjected secondary structure analysis of our current protein by the self-optimized prediction method with alignment (SOPMA) and revealed that it contains 52.45 % alpha helix, 11.89 % extended strand, and 26.57 % random coil (Table 1). In proteomics, the most important part is to determine the 3D structure of a protein [25]. In our study, PHYRE2 was used to generate theoretical structure of pscN ATPase with [90.0 % confidence match which implies that overall fold of the model was almost certainly correct and the central core of the model tends to be accurate [26].…”
Section: Discussionmentioning
confidence: 99%